2019
DOI: 10.1038/s41598-019-47643-1
|View full text |Cite
|
Sign up to set email alerts
|

Neural indices of listening effort in noisy environments

Abstract: Listening in a noisy environment is challenging for individuals with normal hearing and can be a significant burden for those with hearing impairment. The extent to which this burden is alleviated by a hearing device is a major, unresolved issue for rehabilitation. Here, we found adult users of cochlear implants (CIs) self-reported listening effort during a speech-in-noise task that was positively related to alpha oscillatory activity in the left inferior frontal cortex, canonical Broca’s area, and inversely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(136 citation statements)
references
References 73 publications
6
104
1
Order By: Relevance
“…Similarly, highest alpha power was obtained at intermediate . Although increased alpha power has been associated with increased demands or effort (Obleser et al, 2012;Dimitrijevic et al, 2019), to our knowledge no research has shown a peak-shaped behavior for alpha power similar to the present study.…”
Section: Different Measures Reflect Different Aspects Of Listening Efsupporting
confidence: 70%
See 4 more Smart Citations
“…Similarly, highest alpha power was obtained at intermediate . Although increased alpha power has been associated with increased demands or effort (Obleser et al, 2012;Dimitrijevic et al, 2019), to our knowledge no research has shown a peak-shaped behavior for alpha power similar to the present study.…”
Section: Different Measures Reflect Different Aspects Of Listening Efsupporting
confidence: 70%
“…Finally, phase synchronization as well as alpha power were normalized per repetition, SNR and participant. In previous studies, alpha power is often normalized against a baseline period before the stimulation (Obleser et al, 2012;Dimitrijevic et al, 2019). We did not do this because we wanted to compare the five effort measures, so we normalized each measure the same way, i.e.…”
Section: Signal Processing: Phase Synchronization and Alpha Powermentioning
confidence: 99%
See 3 more Smart Citations